Analysis of Utilization of Digital Communication and Information Technology at the Education Office of North Sumatra - Ridho Amansyah, Muhammad; Hafadzly Nasution, Tegar (Journal of Computer Science and Informatics Engineering, 2023)
By utilizing current technology and information, one of the supporting factors must be in the form of human resources capable of managing and operating the technology and providing improvements to the performance of the parties involved. Each instance should have a party that has a high performance value to increase the likelihood of success in achieving its goals. Performance also has an important role for individuals to be able to complete each task and responsibility in order to feel a sense of pride for an achievement. Based on the type of research approach data, this research belongs to a qualitative approach, in which the subjects studied are holistic in nature accompanied by the use of various scientific methods. By conducting this research, it will be seen that utilizing information technology will have a very good impact, especially for employees of the North Sumatra Education Office. This can increase motivation to study independently, maximize individual abilities, and facilitate the stage of receiving information and the opportunity to explore more optimally.